The European and Mediterranean species of Aglaophenia (Cnidaria: Hydrozoa - Svoboda, A.; Cornelius, P. F. S. (Zool. Verh., Leiden, 1991)
The eleven species of the hydroid genus Aglaophenia Lamouroux, 1812, recorded from European and Mediterranean waters are redescribed in detail and aspects of their biology discussed. A section on the identification of the European and Mediterranean species and a comprehensive glossary are included. Comments are given on type specimens, reproduction, ecology and distribution and, briefly, on other biological aspects. Certain of the species occur further north than previously realized. A. acacia Allman, 1883 and A. parvula Bale, 1882, are newly recorded from British waters, the latter being almost new to Europe. It differs only minutely from the widely-known A. pluma. A. kirchenpaueri (Heller, 1968) is added to the Irish faunal list, and has only recently been confirmed as present in British waters. Re-identifications are made of some specimens about 250 years old probably collected by John Ellis and forming part of the Linnean collection in London. Type specimens are discussed, newly identified, or designated, as follows: Aglaophenia lophocarpa Allman, 1877 (lectotype, p. 22); A. parvula Bale, 1882 (lectotype, p. 25); A. pluma (Linnaeus, 1758, as Sertularia) (neotype, p. 30); A. tubulifera (Hincks, 1861, as Plumularia) (holotype identified, p. 36). Other species mentioned are Aglaophenia elongata, A. harpago, A. octodonta, A. picardi and A. tubiformis.Descriptors: AGLAOPHENIA ELONGATA; AGLAOPHENIA HARPAGO; AGLAOPHENIA OCTODONTA; AGLAOPHENIA PICARDI; AGLAOPHENIA TUBIFORMIS; AGLAOPHENIA ACACIA new record; AGLAOPHENIA PARVULA new record; AGLAOPHENIA PLUMA; AGLAOPHENIA KIRCHENPAUERI; AGLAOPHENIA LOPHOCARPA; AGLAOPHENIA TUBULIFERA; SERTULARIA; PLUMULARIAfigs 1-25, tab. 1. (24.xii.1991).